Promoting teacher competencies towards sustainability conducted through STEAM interventions in IndagaSTEAM Escuela Project. - Lupión-Cobos, Teresa; Alarcón-Orozco, Marta; Lechuga-Jiménez, Clotilde (My University, 2023)
Education improves constantly, so lifelong learning and continuing education/professional development are a way of being updated on almost every innovative knowledge approach and learning strategy. STEM education contributes to scaffold a holistic educational framework curriculum. In this line, to establish School Culture supporting STEM education is relevant to foster an education reform at all levels. Place-based learning STEM approach in real-life contexts provides school subjects meaningful elements either for teachers/professors or students. Furthermore, when implementing constructivist teaching-learning approach, problem-based learning, and connections with real world items in the classroom, STEM approach is very efficient, specially using inquiry-based strategies. However, STEM Education goal refers to a holistic integration of STEM areas across the curriculum, although it seems to lack specific scientific literature related to how STEM acronym (and disciplines) should be implemented, because the whole is greater than the sum of its parts. IndagaSTEAM Escuela Project is an experience to promote transfer of learning for students during their teacher training at schools -for compulsory education- to develop students' key competencies, conducted through cooperation between schools and universities by mentoring interventions. The Project program considers the following points: a) Teacher/Student centered approach, b) A curricula reform, new organizational system and new teaching materials, c) HE & School projects implementing inquiry-based learning and place-based learning, d) Teaching and activities selection and design for Professionals and Students, and e) Activity impact evaluation to aim the goal. The program professional development of participants (teachers) is mainly focused on empowering and motivating learners to become active sustainability citizens, fostering critical thinking, and participating in shaping a sustainable future.
Keywords: Ciencia - Estudio y enseñanza; Profesores - Formación profesional; Tecnología - Estudio y enseñanza; Teacher competencies; ODS; STEAM; IndagaSTEAM Escuela Project; PBL STEAM